Radiographic Assessment of the Technical Quality and Periapical Health of Root-Filled Teeth Performed by General Practitioners in a Turkish Subpopulation - E. Tarim Ertas; H. Ertas; Y. Sisman; B. Sagsen; O. Er (The Scientific World Journal)
Aim. The aim of this study was to evaluate by means of radiographs the technical quality of root fillings performed by dental practitioners. Methods and Material. Standardized periapical radiographs were made on 484 patients who received endodontic treatment in private practice. A total of 831 endodontically treated teeth with 1448 roots were evaluated for technical quality of the root canal filling and the periapical status of the teeth. Also, the apical status of each root-filled tooth was assessed according to the length, density, and taper of root fillings, and the presence of apical transportation, broken root instruments, and overfilled sealer or gutta-percha material was recorded for each root canal. Results. Of the endodontically treated teeth 26.6% had healthy periapical tissues, while technically good endodontic treatment constituted 12.8%. Based on the treatment success, there was no significant difference between the tooth groups. Statistical analysis of the data did not demonstrate statistically significant differences between the various parameters that were evaluated (). Conclusions. Technical quality of root fillings in a population who received treatment in private practice was poor and was consistent with a low prevalence of apical health. The probable reasons for this failure are multifactorial and may be improved if the operators improve their skills with continuing postgraduate education programs.